Chronic use of renin‐angiotensin‐aldosterone system blockers and mortality in COVID‐19: A multicenter prospective cohort and literature review. (16th May 2021) - Gault, Nathalie; Esposito‐Farèse, Marina; Revest, Matthieu; Inamo, Jocelyn; Cabié, André; Polard, Élisabeth; Hulot, Jean‐Sébastien; Ghosn, Jade; Chirouze, Catherine; Deconinck, Laurène; Diehl, Jean‐Luc; Poissy, Julien; et al.
Abstract: Aims: The role of renin‐angiotensin‐aldosterone system (RAAS) blockers on the course of coronavirus disease 2019 (COVID‐19) is debated. We assessed the association between chronic use of RAAS blockers and mortality among inpatients with COVID‐19 and explored reasons for discrepancies in the literature. Methods and results: We included adult hypertensive patients from a prospective nationwide cohort of 3512 inpatients with COVID‐19 up to June 30, 2020. Cox proportional hazard models with various adjustment or propensity weighting methods were used to estimate the hazard ratios (HR) of 30‐day mortality for chronic users versus non‐users of RAAS blockers. We analyzed data of 1160 hypertensive patients: 719 (62%) were male and 777 (67%) were older than 65 years. The main comorbidities were diabetes ( n = 416, 36%), chronic cardiac disease ( n = 401, 35%), and obesity ( n = 340, 29%); 705 (61%) received oxygen therapy. We recorded 135 (11.6%) deaths within 30 days of diagnosis. We found no association between chronic use of RAAS blockers and mortality (unadjusted HR = 1.13, 95% CI [0.8–1.6]; propensity inverse probability treatment weighted HR = 1.09 [0.86‐1.39]; propensity standardized mortality ratio weighted HR = 1.08 [0.79–1.47]). Our comprehensive review of previous studies highlighted that significant associations were mostly found in unrestricted populations with inappropriate adjustment, or with biased in‐hospital exposure measurement. Conclusion: Our results do not support previous concerns regarding these drugs, nor a potential protective effect as reported in previous poorly designed studies and meta‐analyses. RAAS blockers should not be discontinued during the pandemic, while in‐hospital management of these drugs will be clarified by randomized trials. NCT04262921.